Asterostromella roseola Bres. ex Rick is combined in Dendrocorticium (Corticiaceae, Agaricomycetes) - Baltazar, Juliano M. (2013)
Examination of the original material of Asterostromella roseola Bres. ex Rick confirmed that it is a good morphological species, characterized by simple-septate generative hyphae, dendrohyphidia and halocystidia, and hyaline, smooth, IKI- basidiospores. Its morphological affinities with current accepted corticioid genera are discussed, and the new combination Dendrocorticium roseolum is proposed. A lectotype is selected and description and drawings are provided.